Evaluation of a computerised physician order entry system. Issue 2 (12th March 2012) - Hofer-Dückelmann, C.; Prinz, E.; Beindl, W.; Berger, K.; Fellhofer, G.; Mutzenbach, J.S.; Schuler, J.
Abstract : Background: In a study evaluating polypharmacy in a cohort of older internal-medicine patients in Austria, inappropriate prescribing and adverse drug events (ADEs) were highly prevalent. According to the literature, computerised physician order entry systems (CPOESs) improve medication safety. Purpose: To implement a CPOES and to evaluate its benefit and acceptance. Materials and methods: A study group of 3 clinical pharmacists, 2 cardiologists and a study nurse implemented and evaluated the Rp-Doc CPOES on two surgical, two internal and one neurological ward from November 2009 to April 2010. Depending on the ward, the support given by the study group in entering data into the system was organised differently. The acceptance of Rp-Doc by its users was evaluated by a questionnaire. Results: During the study period, 1259 patients were admitted. The medication of 560 patients (44%) was documented and analysed by Rp-Doc. Depending on the support that was given, Rp-Doc was used more or less (28-65%). Rp-Doc identified potential drug-drug interactions, wrong doses, duplicated medicines, contraindications and inappropriate medicines. In a questionnaire returned by 18 users, the time that was needed to document the data was considered too long, the alert overkill concerning potential drug-drug interactions and the lack of recommendation of alternatives in case a drug was considered inappropriate were criticised. The information regarding dosing, contraindications and drug adjustment in renal failure was appreciated. The majority felt that the system increased their vigilance regarding drug-drug interactions (69%), ADEs (58%), prescribing in the older (50%) and awareness of cost (27%). There was a lack of personal computers, staff and time to really use the advantages of the CPOES. Conclusions: To implement a CPOES successfully, sufficient professional support and adequate infrastructure are necessary. Once implemented, it would improve medication safety and help to identify those patients who are in greatest need of pharmaceutical care.